2021
DOI: 10.3390/agronomy11071380
|View full text |Cite
|
Sign up to set email alerts
|

Oil Palm Inflorescence Sex Ratio and Fruit Set Assessment in dura × pisifera Biparental Progenies on Fibric Peat Soil

Abstract: This study investigated oil palm inflorescence sex ratio (ISR) and fruit set (FS) yield among 24 dura × pisifera biparental progenies on fibric peat soil, hybridized from ten genetic origins. Three-month intervals of data collection on ISR and “S-shape” procedure for FS determination were carried out in an independent complete randomized design for one year. Based on the assessment of individual progenies, analysis of variance revealed the existence of genetic heterogeneity. Five of the progenies had the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The hatch & carry technique has been applied in several orchards in Indonesia and has succeeded in increasing the initial fruit set. This technique is generally performed on TM 1-3 which has a low fruit set value and a very high-interest sex ratio [13].…”
Section: Fruit To Bunchmentioning
confidence: 99%
“…The hatch & carry technique has been applied in several orchards in Indonesia and has succeeded in increasing the initial fruit set. This technique is generally performed on TM 1-3 which has a low fruit set value and a very high-interest sex ratio [13].…”
Section: Fruit To Bunchmentioning
confidence: 99%
“…Several factors can increase male inflorescence production, including planting material, frond production, soil type, and palm age. Research by Swaray et al [ 5 ] revealed that both oil palm frond production and soil type play a significant role in male inflorescence production. Specifically, peat soil and tissue-cultured planting materials have been found to result in a decline in male inflorescence production.…”
Section: Inadequate Pollen Deposition and Pollen Qualitymentioning
confidence: 99%
“…Therefore, oil palm breeders should prioritize breeding and selecting high-quality planting materials that produce male flowers with viable pollen. Among oil palm DxP progenies, Deli Serdang × Cameroon has been reported to have the highest production of male inflorescences, with a mean value of 29.40% [ 5 ]. Another factor that can influence male inflorescence production in oil palm is aging, as reported by Corley and Gray [ 101 ], who found that the inflorescence sex ratio declines from 90% to below 60% as the palm ages when cultivated on Malaysia’s coastal soils, with cultivation ages of 4 and 15 years, respectively, after planting.…”
Section: Inadequate Pollen Deposition and Pollen Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The number OPD bunches is higher than the actual because it is calculated based on total potential bunches that can be harvested over the next 18 months without any reduction over failure of inflorescence development. Whereas potential availability of number of ripe bunches that can be harvested after the sex determination phase can be reduced because of abortion of female flowers and bunch failure [11,47,50]. Based on actual bunch number, percentage error of OPD prediction between 10 -32% can be combined with other factors to determine value of correction factor for bunch loss.…”
Section: Figure 3 Comparison Production Of Bunch Number Based On Opd ...mentioning
confidence: 99%